2021
DOI: 10.1097/cnd.0000000000000355
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Treatment Response in Immune-Mediated Small Fiber Neuropathy with Trisulfated Heparin Disaccharide or Fibroblast Growth Factor Receptor 3 Antibodies

Abstract: Objective:Novel antibodies to trisulfated heparin disaccharide (TS-HDS) and fibroblast growth factor receptor 3 (FGFR-3) have been recently described in otherwise cryptogenic small fiber neuropathy (SFN) cases. Our goal was to further describe clinical features in such cases and to analyze treatment responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
29
3
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 19 publications
8
29
3
2
Order By: Relevance
“…168,169 Antibodies binding to trisulfated heparin disaccharide (TS-HDS), 191,192 and the intracellular domain of the fibroblast growth factor receptor 3 (FGFR3) 193 have been detected in patients with apparently idiopathic sensory neuropathy, often with features of sensory neuronopathy, 193 including NLD-SFN. [170][171][172][173][174] It is still unclear whether these are autoantibodies playing a pathogenic role or are only biomarkers of a dysimmune process, and whether they can identify patients who would respond to immune intervention. 194 Finally, predispositions towards dysimmunity in some patients with idiopathic SFN is suggested by findings of minor abnormalities of immune and inflammatory biomarkers, 42,115,195 as also observed in NLD-SFN.…”
Section: Associated Conditionsmentioning
confidence: 99%
“…168,169 Antibodies binding to trisulfated heparin disaccharide (TS-HDS), 191,192 and the intracellular domain of the fibroblast growth factor receptor 3 (FGFR3) 193 have been detected in patients with apparently idiopathic sensory neuropathy, often with features of sensory neuronopathy, 193 including NLD-SFN. [170][171][172][173][174] It is still unclear whether these are autoantibodies playing a pathogenic role or are only biomarkers of a dysimmune process, and whether they can identify patients who would respond to immune intervention. 194 Finally, predispositions towards dysimmunity in some patients with idiopathic SFN is suggested by findings of minor abnormalities of immune and inflammatory biomarkers, 42,115,195 as also observed in NLD-SFN.…”
Section: Associated Conditionsmentioning
confidence: 99%
“…48 Eight of the seropositive patients improved on IVIGs, with a 42% reduction in pain scores (p = 0.02), a 44% reduction in the Utah Neuropathy Score, and improved IENFD post-treatment. 48 In another study of idiopathic SFN with IVIG, no significant therapeutic benefit could be documented, why it was concluded that the use of IVIG for idiopathic SFN should be discouraged. 5 In a study of two patients with Ehlers-Danlos syndrome, immune-mediated SFN was suspected and successfully treated with IVIG.…”
Section: Immunoglobulinsmentioning
confidence: 91%
“…7 Recently, novel antibodies to tri-sulfated heparan disaccharide (TS-HDS) and to fibroblast growth factor receptor-3 (FGFR-3) have been found in otherwise cryptogenic SFN cases. 47,48 Whether they can serve as biomarkers of SFN, however, remains speculative. CCM has shown that not only the number of small fibers is reduced but also the number of Langerhans cells.…”
Section: Secondary Sfnmentioning
confidence: 99%
See 2 more Smart Citations